Rendahnya Dukungan terhadap Partai Demokrasi Indonesia Perjuangan di Sumatera Barat, Indonesia - Afriandi, Fadli (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2021)
Partai Demokrasi Indonesia Perjuangan (PDI Perjuangan) is a strong party in Indonesia winning three presidential elections in 1999, 2014 and 2019. However, it got low people’s votes in some provinces like Sumatera Barat. This article explains why PDI Perjuangan got little votes in Sumatera Barat by using the concept of populism as its analytical framework. The required data were collected through interviews and literature study, and were analyzed through qualitative approach. This article argues that the loss of PDI Perjuangan in presidential elections in Sumatera Barat is closely related to the people’s perception of the party as less populist than its competing parties. The people of Sumatera believed that PDI Perjuangan had no sensitivity to their unique characteristics and developed party identities and policy that were considered in contradiction with their social and cultural background. This impacted on Joko Widodo’s low support and votes in 2014 and 2019 presidential elections. He was perceived to have leadership style and characteristics that were not in line with the expectation of Sumatera Barat people, and have issued policies considered unsupportive of people interest.